An ultra-thin flexible wearable sensor with multi-response capability prepared from ZIF-67 and conductive metal–organic framework composites for health signal monitoring. Issue 23 (3rd November 2022) - Zhao, Youwei; Li, Xiang; Yuan, Tian; Huang, Shuhong; Jiang, Ronghui; Duan, Xuefei; Li, Ling; Li, Xiaoting; Zhang, Wenming
Abstract : The first synthesized cZIF-67@Cu-CAT nanoparticles were used as sensitive materials to prepare a dual response mode sensor. Abstract : Simulation of somatosensory systems in human skin with electronic devices has broad applications in the development of intelligent robots and wearable electronic devices. Here, we give an account of a new biomimetic flexible dual-mode pressure sensor, which is based on the first developed sea dandelion-like conductive metal–organic framework (cZIF-67@Cu-CAT) and the self-synthesized mechanically luminescent zinc sulfide nanoparticles and cleverly combines the microdome structure of the lotus leaf. According to finite element simulation analysis (FEA), the deformation behavior and pressure distribution of the contact interface with dandelion-like nanostructures cause the contact area of the sensor to increase rapidly and steadily with the load. It is for this reason that the piezoresistive pressure sensor has a high sensitivity of 71.74 kPa −1 over a wide range of 0.5 to 80 kPa. More importantly, it can roughly perceive stress changes in the external environment through mechanoluminescence materials without a power supply. The ultra-thin flexible pressure sensor is suitable for sensitive monitoring of small vibrations, including wrist pulse and joint motion. Combined with Bluetooth data transmission, it is not difficult to see that the high-sensitivity ultra-thin sensor designed in this study has broad potential in the applications of bio-wearable electronics and will play an immeasurable role in various sports training and joint protection in the future.